Machine Learning for Glacier Monitoring in the Hindu Kush Himalaya - Baraka, Shimaa; Akera, Benjamin; Aryal, Bibek; Sherpa, Tenzing; Shresta, Finu; Ortiz, Anthony; Sankaran, Kris; Lavista Ferres, Juan M.; Matin, Mir; Bengio, Yoshua (NeurIPS CCAI, 2020)
Glacier mapping is key to ecological monitoring in the hkh region. Climate change poses a risk to individuals whose livelihoods depend on the health of glacier ecosystems. In this work, we present a machine learning based approach to support ecological monitoring, with a focus on glaciers. Our approach is based on semi-automated mapping from satellite images. We utilize readily available remote sensing data to create a model to identify and outline both clean ice and debris-covered glaciers from satellite imagery. We also release data and develop a web tool that allows experts to visualize and correct model predictions, with the ultimate aim of accelerating the glacier mapping process.